Species–area relationship and small‐island effect of vascular plant diversity in a young volcanic archipelago. (8th September 2021) - Chiarucci, Alessandro; Guarino, Riccardo; Pasta, Salvatore; Rosa, Alfonso La; Cascio, Pietro Lo; Médail, Frédéric; Pavon, Daniel; Fernández‐Palacios, José María; Zannini, Piero
Abstract: Aims: Aeolian islands form an active volcanic archipelago. By using updated vascular plant checklists for islands and islets, we tested four hypotheses: (i) Island species–area relationship (ISAR) of alien species has lower c ‐ and higher z ‐values than native species, (ii) islands with active volcanoes have lower species richness than expected for native and alien species, (iii) ISAR of native species shows lower c ‐ and higher z ‐values than ISARs of Mediterranean land bridge archipelagos and (iv) species richness of smaller islets is independent of area. Location: Aeolian Archipelago, Mediterranean Basin. Taxon: Vascular plants, identified and named according to the Flora of Italy (Pignatti et al., 2017–2019). Methods: Checklists of native and alien plant species were obtained for eight islands and 24 islets. ISARs were fitted by the Arrhenius power function ( S = c · A z ) and used to test the first two hypotheses. The third hypothesis was tested by comparing ISAR of Aeolian Archipelago to those from other central and eastern Mediterranean archipelagos. The fourth hypothesis was tested by fitting models defining the presence and limit of the small‐island effect. Results: The checklists included 894 species—749 native and 145 alien. ISARs fitted well for native and alien species and resulted in typical values of c and z parameters. The first and second hypotheses were supported by model fitting. The third hypothesis was not confirmed by the comparison of the ISAR of the Aeolian Archipelago with other archipelagos. The small‐island effect predicted by the fourth hypothesis was supported using S versus LogA for both native and alien species, while for native species it was supported also using the log transformation of the Arrhenius model. Main conclusions: We reported a first comprehensive analysis of plant species richness in the unique Aeolian Archipelago, verifying typical ISARs, no peculiarity with respect to land bridge archipelagos and a somewhat unclear signal for the small‐island effect.